Computational performances of a simple interchange heuristic for a scheduling problem with an availability constraint - Moncel, Julien; Thiery, Jérémie; Waserhole, Ariel (Computers & industrial engineering, 2014)
•We address a scheduling problem subject to an unavailability constraint.•We study an existing interchange heuristic to minimize the total-flow time.•We improve the theoretical error bound of this heuristic and prove its tightness.•We provide computational experiments of this heuristic.•These experiments demonstrate the relevance of the algorithm for applications. This paper deals with a scheduling problem on a single machine with an availability constraint. The problem is known to be NP-complete and admits several approximation algorithms. In this paper we study the approximation scheme described in He et al. [Y. He, W. Zhong, H. Gu, Improved algorithms for two single machine scheduling problems, Theoretical Computer Science 363 (2006) 257–265]. We provide the computation of an improved relative error of this heuristic, as well as a proof that this new bound is tight. We also present some computational experiments to test this heuristic on random instances. These experiments include an implementation of the fully-polynomial time approximation scheme given in Kacem and Ridha Mahjoub [I. Kacem, A. Ridha Mahjoub, Fully polynomial time approximation scheme for the weighted flow-time minimization on a single machine with a fixed non-availability interval, Computers and Industrial Engineering 56 (2009) 1708–1712].